Modification of the Scarf Osteotomy for Treatment of Hallux Valgus. Issue 4 (December 2015) - Wright, Jonathan; Choudhury, Mahbuba; Charalambides, Charalambos
Abstract : Scarf osteotomy is a technique in the management of hallux valgus, which has been seen to grow in popularity in recent years, mainly because of its versatility in correction of the deformity. We describe a modification of the technique for the Scarf osteotomy to utilize the excised bone, produced as part of the standard technique, as an autologous bone graft. We present the outcomes of a consecutive series of patients operated upon by the senior author, using this technique. Level of Evidence: Treatment Benefits Level 4 (Case series). See Instructions for Authors for a complete description of levels of evidence.